Heterostructured NiFe oxide/phosphide nanoflakes for efficient water oxidation. Issue 23 (22nd May 2019) - Yan, Ailing; Wan, Hao; Chen, Gen; Zhang, Ning; Ma, Wei; Liu, Xiaohe; Cao, Yijun; Ma, Renzhi
Abstract : Heterostructured Ni2/3 Fe1/3 O/Ni4/3 Fe2/3 P nanoflakes could be successfully synthesized via the partial phosphidation of the oxide precursor, which achieved a current density of 10 mA cm −2 at a low overpotential of 273 mV with a small Tafel slope of 79 mV dec −1, superior to single-phase oxide and phosphide nanoflakes. Abstract : To realise the gradual replacement of noble metal-based materials for electrocatalytic energy conversion, numerous studies need to be focused on the compounds based on inexpensive 3d transition metals (such as Fe and Co). For achieving energetic electrocatalysis, elaborately designed nanostructures are urgently desired. Here, we reported a facile approach for the preparation of a NiFe oxide/phosphide (Ni2/3 Fe1/3 O/Ni4/3 Fe2/3 P) heterostructure with a 2-dimensional (2D) nanoflake-like morphology. Based on the combined advantages of composition and structure, the 2D Ni2/3 Fe1/3 O/Ni4/3 Fe2/3 P nanoflakes were characterized to exhibit a high activity for the electrocatalytic water oxidation, surpassing that of individual Ni2/3 Fe1/3 O or Ni4/3 Fe2/3 P nanoplates. This result may offer a great possibility of delicatedly designing nanostructures for highly efficient electrochemical energy conversion.